Effect Of EM4 and Molasses Levels on Quality of Organic Liquid Fertilizer of Cow Urine Based - Kamaliyah, Siti Nurul; Wahyuni, Rini Dwi (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
The research aim was to determine the effect of EM4 and molasses level on the quality of liquid organic fertilizer based on cow urine in terms of total N, C-organic, TDS and pH. The material of liquid organic fertilizer used in this research was cow urine. The method used was an experimental method using a Complete Randomized Design (CRD). The observed variables are total Nitrogen, C-organic content and TDS values. The data obtained were analyzed using analysis of variance. The results of the research of the addition of EM4 and molasses with different levels showed a noticeable difference (P<0.05) in total nitrogen. Meanwhile, C-organic and TDS levels showed a very signifactly difference (P<0.01). The result of this research, the addition of EM4 (20 ml) and molasses (25 ml), namely P1, was able to produce high total N levels and with a TDS that was maximum so as not to reduce the quality of nutrients when applied to plants and the C-organic value was the highest than other treatment. The results of the values on P1 were reviewed from N total 0.316 %, C-organic 56.97%, TDS level 7184ppm and pH value 6.6.